Community-Based Sanitation Management Model Using Local Aspects of Coastal Areas - Susilawati Susilawati; Nefi Darmayanti; Reinpal Falefi; Yusuf Hanafi Lubis (Jurnal Kesehatan Masyarakat, 2023)
Previous findings showed that there are only a few studies on the core problem of environmental sanitation in coastal areas. The study Mawar and Wahidah (2018), the coastal community of Percut Sei Tuan only uses 20% clean water, does not have a latrine 42.9%, and does not have a SPAL of 46.7%. Therefore, this study aims to examine the cultural, gender, and stakeholder aspects of community-based sanitation management (CBSM). A cross-sectional design was used, and the sample population consists of family heads in the Percut Sei Tuan Sub-district. The sample size was calculated using a category survey formula of 414 households from the population. The samples were selected using a simple random sampling technique, and a questionnaire instrument, which was tested for its validity and reliability was used for data collection. The data were then analyzed using CFA (Confirmatory Factor Analysis) to assess the factors that influence CBSM. The results showed that gender roles have a significant effect on environmental sanitation management in coastal areas with a P0.001, and culture has a significant effect on CBSM with a P0.001. However, the role of stakeholders was insignificant in this study. CBSM in coastal areas was still very low in terms of participation in planning, implementation, and utilization. The involvement of women as an aspect of gender in the formation of a disciplined culture in sanitation management is very necessary to mobilize family members.